Quo Vadis Masyarakat Sipil: Normalisasi Relasi Negara dalam Imajinasi Intelektual Jawa Timur - Artha, Gratia Wing (Journal Politique, 2026)
In the post-Reformasi era, Indonesian civil society confronts increasingly complex democratic challenges amidst shifting power dynamics. This research aims to dissect the discourse surrounding the political role of civil society in democratic development through the perspectives of intellectual circles in Surabaya and Malang. Employing a qualitative method rooted in Michel Foucault's discourse analysis, the study explores intellectual viewpoints via in-depth interviews and comprehensive documentary analysis. The findings reveal a fragmentation of discourse into three distinct typologies: critical intellectuals, who emphasize a total oversight function against state power; moderate intellectuals, who advocate for strategic collaboration with the government; and hybrid intellectuals, who promote cooperative engagement while maintaining a rigorous critical distance. This study concludes that the political role of civil society is far from monolithic; rather, it is the product of intellectual contestation shaped by the intricate power relations between scholars and state structures.